Traditions in Arequipa - Díaz, Willard (2023)
In this article, the main narrative modalities of the traditionalists from Arequipa, Mariano Ambrosio Cateriano and Francisco Ibáñez, are presented. The influence of Ricardo Palma in the works of both authors is followed and the differences between each of them are pointed out. In addition, it reveals facts within the literary field that determined the early displacement of the genre of tradition towards the production of modern tales. Keywords: Mariano Ambrosio Cateriano, Francisco Ibáñez, Ricardo Palma, Peruvian Traditions, modern tales.